2018
DOI: 10.1038/s41586-018-0145-8
|View full text |Cite
|
Sign up to set email alerts
|

Insights into catalysis and function of phosphoribosyl-linked serine ubiquitination

Abstract: Conventional ubiquitination regulates key cellular processes by catalyzing the ATP-dependent formation of an isopeptide bond between ubiquitin (Ub) and primary amines in substrate proteins1. Recently, SidE family of bacterial effector proteins (SdeA, SdeB, SdeC and SidE) of pathogenic Legionella pneumophila were shown to utilize NAD+ to mediate phosphoribosyl-linked ubiquitination (PR-ubiquitination) of serine residues in host proteins2,3. Yet, the molecular architecture of the catalytic platform enabling such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
128
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 95 publications
(137 citation statements)
references
References 29 publications
5
128
0
Order By: Relevance
“…SdeA catalytic mechanism is inhibited by adenosine 5′-O-thiomonophosphate, an AMP analogue, that binds with low-affinity the SdeA PDE domain and alters substrate positioning. This finding provides new insights for a rationale designing of novel antimicrobial compounds to inhibit this class of Legionella toxins [248].…”
Section: Adp-ribosylation-dependent Ubiquitination As Mechanism Of Pamentioning
confidence: 85%
See 1 more Smart Citation
“…SdeA catalytic mechanism is inhibited by adenosine 5′-O-thiomonophosphate, an AMP analogue, that binds with low-affinity the SdeA PDE domain and alters substrate positioning. This finding provides new insights for a rationale designing of novel antimicrobial compounds to inhibit this class of Legionella toxins [248].…”
Section: Adp-ribosylation-dependent Ubiquitination As Mechanism Of Pamentioning
confidence: 85%
“…By clarifying the virulence mechanism of SdeA, it has been shown that the ubiquitination induced by Legionella in the host is dependent on ADPr [245]. Structural and biochemical characterisation have revealed that SdeA is a dual enzyme with both MARylation and phosphodiesterase (PDE) activities, due to the presence of two distinct protein folds, namely ARTC-like and PDE domains [245,247,248]. ADPr-dependent ubiquitination of protein substrates catalysed by SdeA is a two-step reaction: first, SdeA transfers ADP-ribose from NAD + onto arginine 42 (Arg42) of an Ubiquitin (Ub) molecule in order to generate an ADP-ribosylated-Ub intermediate; in the second step, phosphodiesterase activity converts ADP-ribosylated-Ub intermediate to phosphoribosyl-Ub which is then conjugated through an ester linkage to a serine residue to target protein or to SdeA itself [245,248].…”
Section: Adp-ribosylation-dependent Ubiquitination As Mechanism Of Pamentioning
confidence: 99%
“…Magnetic forms of graphene would be useful for spintronics, a technology that forms the basis of today's magnetic data storage 3,4 . But the main interest in generating magnetic edge states in graphene is for quantum technologies.…”
Section: F E R N a N D O Lu I S And E U G E N I O C O R O N A D Omentioning
confidence: 99%
“…Once the nicotinamide group from NADH is released from the enzyme, a conformational change can occur, allowing Arg42 to replace Arg72 in the active site. This model explains why ADPR attaches selectively to Arg42 and not to , Dong et al 2 and Kalayil et al 3 report the structure of the enzyme SdeA, and Wang et al 4 present the structure of the enzyme SidE. a, In the first step, the enzyme's mART domain processes NAD + and adds an adenosine diphosphate ribose (ADPR) group to the amino-acid residue arginine 42 (Arg42) of ubiquitin.…”
mentioning
confidence: 99%
See 1 more Smart Citation